Single-Port Laparoscopic Right Hemicolectomy: Intermediate Results - Hopping, Jacob R. (Society of Laparoendoscopic Surgeons, 2013)
BACKGROUND: Single-port laparoscopic colectomy was first described in 2008 as a new technique for colorectal surgery.(1) No available reports have stated the intermediate- or long-term outcome. We report our intermediate results for the first 20 single-port laparoscopic right hemicolectomies performed by a single laparoscopically trained surgeon at our institution. DESIGN: Between February 2009 and September 2010, 20 consecutive patients with an indication for right hemicolectomy who were candidates for laparoscopic surgery underwent a single-port laparoscopic approach. The only exclusion was a previous midline laparotomy. The patients were followed for outcomes after a median of 27 months (range: 15 to 35). RESULTS: The mean age was 65 years (range: 59 to 88). The mean body mass index was 28 (range: 20 to 35). Seventy-five percent of patients had significant comorbidities, with an American Society of Anesthesiologists class of III or IV. The median estimated blood loss was 25 mL (range: 25 to 250). The mean number of lymph nodes was 13 (range: 0 to 29). There was one conversion to hand-assisted laparoscopic colectomy and one to open colectomy secondary to bleeding. The mean hospital stay was 5 days (range: 3 to 7). Thirty-day postoperative complications included 1 wound infection, 1 patient with alcohol withdrawal, and 1 incidence of colitis caused by Clostridium difficile infection. At a median follow-up of 27 months, there were no local recurrences or distant metastases. One death occurred at 17 months from myocardial infarction. Two patients developed incisional hernias, with one requiring a laparoscopic hernia repair. One patient required a completion proctocolectomy for a pathological diagnosis of hyperplastic polyposis syndrome. CONCLUSIONS: Single-port laparoscopic right hemicolectomy has been safely performed in patients who are candidates for conventional laparoscopic hemicolectomy. This small series indicates that intermediate-term results are similar to conventional laparoscopic surgery in efficacy, safety, and oncological outcomes. Larger datasets are necessary to determine cost-effectiveness, differences in postoperative outcomes, and patient satisfaction.